26. ANALGESIC EFFICACY OF ULTRASOUND-GUIDED FASCIA ILIACA COMPARTMENT BLOCK COMPARED TO INTRATHECAL MORPHINE AFTER PROXIMAL FEMORAL FRACTURE SURGERY (Vietnam Journal of Community Medicine, 2025)
Objective: To compare the analgesic efficacy and adverse effects between ultrasound-guided fascia iliaca compartment block and intrathecal Morphine in patients after proximal femoral fracture surgery.Subjects and methods: A clinical trial was conducted on 60 patients undergoing proximal femoral surgery at Hue University of Medicine and Pharmacy Hospital from April 2024 to August 2025. Patients in the intervention group received fascia iliaca compartment block above the inguinal ligament using 0.25% Levobupivacaine. Pain was assessed using the VAS, along with evaluation of adverse effects, rescue Morphine consumption, and patient satisfaction within 24 hours postoperatively.Results: Fascia iliaca compartment block above the inguinal ligament provided effective analgesia, with mean resting and movement VAS scores at all time points being below 4. The mean 24-hour rescue Morphine consumption was 5.0 ± 0.74 mg, with a mean time to first rescue dose of 10.83 ± 5.37 hours. Patient satisfaction (satisfied or very satisfied) with analgesia was significantly higher in the intervention group (63,3%) compared with the control group (30%).Conclusion: Ultrasound-guided fascia iliaca compartment block is an effective and safe analgesic method after femoral neck fracture surgery, and may reduce the adverse effects, and improving patient stisfaction compared with intrathecal Morphine.
Keywords: Fascia iliaca compartment block, intrathecal Morphine, postoperative analgesia, femoral neck fracture.